Family Developmental Tasks and Socialization Skills in Children with Special Needs: Yunita Ery Susanty, Yesi Puspita Sari, Adaniaty Rohana Uly - Yunita Ery Susanty; Yesi Puspita Sari; Adaniaty Rohana Uly (STIKes Persada Husada Indonesia, 2026)
Research Objective: Family developmental tasks during the school-age period include supporting children’s intellectual growth, independence, and socialization outside the home. For children with special needs, family support is particularly important because social interaction may be affected by communication, behavioral, or adaptive difficulties. This study aimed to analyze the relationship between family developmental tasks in school-age children and the socialization skills of children with special needs at SLBN 01 North Bengkulu. Methodology: A quantitative analytic study with a cross-sectional design was conducted at SLBN 01 North Bengkulu in January 2026. The study involved 26 parents of children with special needs selected using purposive sampling. Data were collected using structured questionnaires measuring family developmental task achievement and children’s socialization skills. The data were analyzed using univariate analysis and the Chi-Square test with a significance level of 0.05. Results: Most respondents were female (69.2%). Family developmental tasks were fully achieved by 18 respondents (69.2%), and good socialization skills were reported in 17 children (65.4%). Bivariate analysis showed a significant relationship between family developmental tasks and children’s socialization skills (p < 0.001). Conclusion: The achievement of family developmental tasks is significantly associated with better socialization skills among children with special needs. Strengthening family-centered support, parental guidance, and school-family collaboration is recommended to improve social development outcomes.